Implementasi Mudharabah Dalam Pengelolaan UMKM Slow Bar Coffee Jebres - Aulia, Nurul; Bagaskara, Andhika (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
Coffee is one of the culinary businesses that is popular with Indonesian people, whether they are just sitting back enjoying the atmosphere or taking it home. Slow Bar Coffee is present as an innovation in the culinary world which is generally not too big, the chairs are arranged in a row and the number of chairs is also very small. Slow Bar Coffee customers can find out what type of coffee they want to drink and experienced baristas provide coffee knowledge and information. The aim of this research is to determine the implementation of mudharabah. This research is a qualitative research. Primary data was collected through observation and interviews with Slow Bar Coffee managers. The research results show that the management of Slow Bar Cofee implements Mudharabah Muthlaqoh because the management of Slow Bar Cofee in the management of Mudharabah Muthlaqoh mudharib is not tied to location and management concept even though there is collaboration between shahibul maal who provides capital and mudharib who manages Slow Bar Cofee.